CLEAN ARCHITECTURE: how to minimize the cost of software - Donato, Daniel Poletto; Zuchi, Jederson Donizete (Revista Interface Tecnológica, 2021)
This study aims to demonstrate, through literary reference, what are the performance and cost advantages of using the clean architectural and code pattern for software development. Based on the theoretical support, examples of architectural and development decisions will be demonstrated, as well as the use of a tool to analyze the code pattern and verify if it needs to be rewritten because it is connecting to an unclean path or by inflicting as validations defined by literary authors and the analysis tool. With the results, it was possible to observe the loss of productivity and the increase in the cost of the software with each new deployment, which occurs due to the difficulty of understanding the maintenance of software that did not follow the aforementioned pattern and inflicted restrictions on the maintenance of a readable código. This increase is around 80%, as the cost of a software is dedicated to its maintenance.
Keywords: Architecture; Code; Clean